Doping effects of fluorinated organic dyes on the open-circuit voltage of bulk-heterojunction photovoltaic devices. (11th June 2015) - Watanabe, Tomoki; Yamashita, Kenichi
Abstract: We have investigated photovoltaic properties of bulk-heterojunction (BHJ) organic absorption layer doped with fluorinated Coumarin dyes. By dilute doping of a fluorinated Coumarin dye, Coumarin 307, into poly(3-hexylthiophene-2, 5-diyl) (P3HT) and [6, 6]-phenyl-C61-butyric acid methyl ester (PCBM) BHJ absorption layer, the open-circuit voltage of photovoltaic device increased by ∼90 mV without the significant degradation in the short-circuit current density. On the other hand, the doping of non-fluorinated Coumarin dye such as Coumarin 2 did not induce such the enhancement effect in the open-circuit voltage. In ultraviolet photoelectron spectroscopies, the doping of Coumarin 307 was found to have no impact on P3HT, but the density of state of PCBM was significantly modified by the doping. The change in the density of state was confirmed also in ultraviolet absorption measurement. Possible explanations for the enhancement in the open-circuit voltage are discussed from the experimental results, and a shift of the vacuum level by the doping can be considered as a direct origin.